Housing for village hens - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Maurice Munyenyembe, and expert with the FAO in Malawi, explains the important principles in building appropriate housing for village chickens.